Adjustment to fibromyalgia: the role of domain-specific self-efficacy and acceptance - Sahar, Karan; Thomas, Shirley A.; Clarke, Simon P. (Wiley, 2015)
Objective Fibromyalgia is a long‐term condition of unknown aetiology characterised by widespread pain, fatigue, joint stiffness, and tenderness. Research in long‐term conditions traditionally focuses on negative aspects of coping. The objective of this study therefore was to investigate the role of positive factors such as self‐efficacy and acceptance in the context of adjustment to fibromyalgia.